Impact of Organizational Justice on Organizational Commitment: The Intermediate Role of Emotional Intelligence in Jordanian Telecom Companies - Alzawahreh, Laith Ibrahim; Al Omari, Ghassan Issa (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of the study is measuring the impact of organizational justice on the organizational commitment: The intermediate role emotional intelligence at the Jordanian communication companies. The sample of the study consisted of (320) employees. The study adopted the descriptive analytical method. In order to collect and analyze data, the survey study tool was distributed. The study reached at several results as follows Jordanian telecom operators apply regulatory justice, organizational commitment, and emotional intelligence to a high degree. The study recommended Jordanian Telecom companies should enhance the organizational justice since it plays an active role in shaping the employees’ positive behaviors and reduce their negative behaviors Jordanian Telecom companies should recognize the importance of organizational commitment of employees because if its role in creating a job stability.